2014
DOI: 10.1093/jjco/hyu100
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative Radiotherapy for the Treatment of Malignant Solitary Fibrous Tumor of the Nasal and Paranasal Area

Abstract: This is the first attempt to successfully combine cytoreductive surgery with intensity modulated radiation therapy and stereotactic body radiation therapy together to treat solitary fibrous tumor of the nasal and paranasal area, which may provide a potential strategy for the treatment of similar cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
20
0
1
Order By: Relevance
“…Therefore, there is an overall good behavior with low local recurrence rate, different from other anatomic sites [39]. Although not reported in the sinonasal tract, SFTs in patients [55 years, with large tumors ([15 cm), with necrosis, increased mitotic activity and/or pleomorphism or incomplete resection are designated as ''malignant'' or ''dedifferentiated'' SFT [40,41], associated with metastasis and disease-specific mortality [42]. Treatment of sinonasal tract SFTs is usually by complete excision or by wide excision.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Therefore, there is an overall good behavior with low local recurrence rate, different from other anatomic sites [39]. Although not reported in the sinonasal tract, SFTs in patients [55 years, with large tumors ([15 cm), with necrosis, increased mitotic activity and/or pleomorphism or incomplete resection are designated as ''malignant'' or ''dedifferentiated'' SFT [40,41], associated with metastasis and disease-specific mortality [42]. Treatment of sinonasal tract SFTs is usually by complete excision or by wide excision.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…While the rarity of SFT/HPCs has limited the study of adjuvant therapies, a number of small case series have observed prolonged tumor-free survival when radiation is combined with surgical resection [25,26,27], suggesting that adjuvant therapy may be of benefit after gross total resection in certain patients. The role of chemotherapy is even less defined, particularly as it has typically been reserved for salvage therapy in progressive SFT no longer amenable to resection.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary fibrous tumors (SFTs) most often originate in the pleura, with other common sites of occurrence including the extremities, mediastinum, peritoneum, and orbit [4]. The key diagnostic criterion of these tumors is their immunohistochemical reactivity, with CD34 and STAT6 being the most commonly observed cell markers [2,5-6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Doyle, et al reports that 98% of tumors expressing STAT6 are confirmed to be SFTs [7]. These tumors are rarely malignant, but 10%-15% may metastasize to the lungs, bones, and liver [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation